2013
DOI: 10.1371/journal.pone.0055768
|View full text |Cite
|
Sign up to set email alerts
|

Basis for Cumulative Cultural Evolution in Chimpanzees: Social Learning of a More Efficient Tool-Use Technique

Abstract: BackgroundThe evidence for culture in non-human animals has been growing incrementally over the past two decades. However, the ability for cumulative cultural evolution, with successive generations building on earlier achievements, in non-human animals remains debated. Faithful social learning of incremental improvements in technique is considered to be a defining feature of human culture, differentiating human from non-human cultures. This study presents the first experimental evidence for chimpanzees' social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 35 publications
2
67
2
5
Order By: Relevance
“…These studies with phylogenetically diverse species show that adaptive social learning rules likely evolved independently in response to particular ecological conditions rather than exclusively in our own species' recent ancestors. Indeed, chimpanzees are surprisingly reluctant to switch to higher-payoff behaviours (Marshall-Pescini and Whiten 2008; although see Yamamoto et al 2013) and while they do exhibit social learning, and this is sometimes labelled 'conformity' (e.g. Whiten et al 2005), conformity has not been demonstrated in chimpanzees in the specific sense of being disproportionately more likely to copy the majority (van Leeuwen and Haun 2013).…”
Section: Social Learning Is Payoff-biased and Conformistmentioning
confidence: 99%
“…These studies with phylogenetically diverse species show that adaptive social learning rules likely evolved independently in response to particular ecological conditions rather than exclusively in our own species' recent ancestors. Indeed, chimpanzees are surprisingly reluctant to switch to higher-payoff behaviours (Marshall-Pescini and Whiten 2008; although see Yamamoto et al 2013) and while they do exhibit social learning, and this is sometimes labelled 'conformity' (e.g. Whiten et al 2005), conformity has not been demonstrated in chimpanzees in the specific sense of being disproportionately more likely to copy the majority (van Leeuwen and Haun 2013).…”
Section: Social Learning Is Payoff-biased and Conformistmentioning
confidence: 99%
“…Many animals engage in social learning (see Galef & Laland, 2005), including chimpanzees (e.g., Bering, Bjorklund, & Ragan, 2000;Whiten, 1998;Yamamoto, Humley, & Tanaka, 2013), orangutans (Pongo pygmaeus; Bering et al, 2000), capuchin monkeys (Cebus apella; Ottoni & Mannu, 2001), and other social mammals, as well as birds, such as ravens (Bugnyar & Kotrschal, 2002), quail (Köksal & Domjan, 1998), and chickens (Nicol, 2006), and fish (e.g., nine-spined sticklebacks, Pungitius pungitius; Kendal, Rendell, Pike, & Laland, 2009), and reptiles (bearded dragon, Pogona vitticeps; Kis, Huber, & Wilkinson, 2015).…”
Section: Social Complexitymentioning
confidence: 99%
“…Thus, we see a modification, in terms of complexity and efficiency, of an existing cultural behavior. However, investigation with captive chimpanzees concluded that cumulative learning of increasingly complex skills may be absent in chimpanzees (Dean et al, 2012; Marshall-Pescini & Whiten, 2008) or limited to small modifications in behavioral efficiency that may easily be invented by a few adept individuals (Yamamoto, Humle, & Tanaka, 2013). In Dean et al (2012) groups of capuchins, chimpanzees, and nursery school children were presented with a puzzle box containing three, increasingly difficult, task solutions.…”
Section: Introductionmentioning
confidence: 99%